Increasing LGBTQ+ inclusion & competency in wildlife sciences: intersections of sociocultural, structural, and historic barriers to inclusion - Nathan B. Alexander; Douglas Knutson; Loren Lynch; Madeleine Spellman; Michael Rivera; Leslie K. Morrow; Maxine Scherz; Thea E. Clarkberg; Lucas T. Allen‐Custodio; Kal Fountain; Isaac Klimasmith; Emmett M. Smith; et al. (Wildlife Society Bulletin, 2024)
Abstract Science has a history of excluding marginalized groups, including people who are lesbian, gay, bisexual, trans, queer, and other marginalized gender and sexual identities (LGBTQ+), and recent calls urge the wildlife sciences to address disparities. Literature on inclusion in the life sciences generally has focused on personal affirmation and has neglected comprehensive discussion of barriers rooted in historical, structural, and sociocultural context. In our literature review, we construct a narrative highlighting the intersections between historic LGBTQ+ exclusion in society and wildlife science due to current policy trends, pressures of cis‐heteronormativity, and survival barriers on LGBTQ+ people in wildlife sciences in the United States. Wildlife scientists must have competency on LGBTQ+ marginalization topics to advance inclusion in our discipline, and this should include comprehension of historic and current legislation and social perceptions. To bolster inclusion efforts, we recommend thoughtful data collection on experiences of LGBTQ+ people within the wildlife sciences. To address root causes of exclusion, institutions and organizations should address disparities in financial support, housing, and physical and mental health resources as part of LGBTQ+ advocacy, in addition to interpersonal efforts.